Clinical cases of an accessory spleen in the pelvic and pelvic splenosis - U. A. Strupeneva; O. A. Efimova-Korzeneva; E. I. Kluchnikova (Медицинский вестник Юга России, 2023)
The article describes cases of diagnosis of an additional spleen in the pelvis and splenosis of the pelvis in women, detected by ultrasound, confirmed by MRI. The relevance of the publication of the presented observations is determined by the rarity of such localization of the spleen and splenosis in the pelvis and the low awareness of obstetricians and gynecologists, most often conducting ultrasound examination of pelvic organs, about this pathology. Cases of an accessory spleen and splenosis in the abdomen are known and written in the literature, while similar findings in the pelvis are, firstly, a rare find, and secondly, ultrasound examination in gynecology is carried out by obstetricians-gynecologists, who rarely meet with surgical pathology, thirdly, the echographic picture requires differential diagnosis with endometrioma, hemangioma, primary and metastatic cancer, and splenosis and accessory spleen should also be differentiated from each other. The article presents two of our own clinical cases of splenosis and accessory spleen with US and MRI data, discusses the reasons for difficulties in diagnosis and key criteria for differential diagnosis, and also includes a review of the literature on this topic. Based on all of the above, it was concluded that should not forget about such a rare but possible diagnosis as pelvic splenosis, and also remember about a possible congenital condition – accessory spleen.